Central de ultrassom: proposta de rastreamento de malformações cardíacas fetais - Barros, Lidiane Pereira dos Reis [UNIFESP] (2016)
Objective: To elaborate a proposal to assist in the identification of fetal cardiac malformations by creating an model Ultrasound Central to be designed in conjunction with a medical training methodology and a computational tool that allows the transmission of fetal heart images through Internet, acquired during obstetric exam or morphological ultrasound performed in a healthcare facility to one or more centers, formed by specialists in fetal cardiology, to assist on the diagnosis. Methods: For the development, the work was organized in three blocks: Research and Development, Methodology and Technological Solution. In block one: Research and Development, the project was conceived and the requirements determined. In block two: Methodology, establishment of a methodology to train obstetricians in the identification of fetal cardiac malformations, through medical training and in block three: Technological Solution, implementation of a system for the operation of the Ultrasound Central and its requirements. Results: Block one results were achieved through the possibility of using various types of ultrasound equipment in the solution, including analogue ones, and allowing the compression of the exams without losing the quality needed for report elaboration. In block two, a training program was developed to train physicians in the recognition of fetal heart malformations and system usage, and in block three, the creation of a viable product to fulfils the flow of the processes designed for the solution, such as, sending of morphological obstetric ultrasound examinations on the Internet, to a central with specialists in ecocardiofetal issue a second opinion of the report or guidance for the accomplishment of the examination, tools for image analysis to evaluate the exam, among others. Conclusion: The three objectives proposed in the thesis were attended, in the spheres of elaboration of the Ultrasound Central model, creation of the methodology to help the identification of fetal cardiac malformations and implementation of the computational tool.